Sharia Marketing and Employee Intelligence on Public Trust in Indonesian Islamic Banking - Muhammad Rijalus Sholihin; Imam Abrori (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2021)
The development of the Islamic banking system in Indonesia is carried out by a dual banking system within the framework of the Indonesian Banking Architecture (API). This has received a good response from the community so that it can create progressive trust. In addition to the sharia system label, there are several aspects that are thought to be factors in increasing public trust, including sharia marketing strategies and employee intelligence. The strategic process is the main pillar in gaining public attraction and trust. Likewise with the capabilities or intelligence of employees which can increase public trust. For this reason, this study aims to examine and analyze Islamic marketing and employee intelligence as an effort to increase public confidence in Islamic banking in Indonesia. This research was conducted in Jember Regency with a sample size of 100 respondents. The analytical method used is multiple linear regression analysis. The results of this study indicate that Islamic marketing has a significant and significant effect on public trust in Islamic banking, while employee intelligence does not show an effect on public trust in Islamic banking. The coefficient of determination obtained with an R Square value of 7.8%, this shows that public trust can be explained by the existence of Islamic marketing and the intelligence of Islamic marketing employees and employee intelligence.